1954
DOI: 10.1021/jf60042a008
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to DDT, DDT-Dehydrochlorinase, an Enzyme Found in DDT-Resistant Flies

Abstract: An enzyme extractable from various strains of DDT-resistant houseflies catalyzes the dehydrochlorination of DDT to form a nontoxic product [1,1 -dichloro-2,2-bis(p-chlorophenyljethylene]. The enzyme requires activation by glutathione. It is irreversibly inhibited at pH 3.5 or lower and has maximum activity at about pH 7.4. Temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…This mechanism is different from the canonical GST detoxification reaction because no GSH-DDT conjugate is formed. 4 GSH-dependent DDTase activity was first discovered in Musca domestica (housefly), 5 and it was then shown that purified housefly proteins with DDTase activity also had biochemical activities typical of GSTs. 6 Since then, GSTs from Drosophila melanogaster, 7 Anopheles gambiae, 2 Anopheles dirus, 8 and Aedes aegypti 9 have been cloned and shown to have DDTase activity.…”
mentioning
confidence: 99%
“…This mechanism is different from the canonical GST detoxification reaction because no GSH-DDT conjugate is formed. 4 GSH-dependent DDTase activity was first discovered in Musca domestica (housefly), 5 and it was then shown that purified housefly proteins with DDTase activity also had biochemical activities typical of GSTs. 6 Since then, GSTs from Drosophila melanogaster, 7 Anopheles gambiae, 2 Anopheles dirus, 8 and Aedes aegypti 9 have been cloned and shown to have DDTase activity.…”
mentioning
confidence: 99%
“…[1] DDTdehydrohalogenases of the house fly had a pH optimum of 7.4. [26] This enzyme is resistant to digestion by proteolytic enzymes as well as high temperature without undergoing denaturation. [1] The enzyme from Pseudomonas putida T5 at acid and alkaline range showed 95.7 and 95.3% lower activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lichtwardt (1964), Tsukamoto and Suzuki (1964), Oppenoorth (1965a, 1965b and Grigolo and Oppenoorth (1966) found that the dominant gene for DDT resistance (variously named R, D-ase, RDDT) in strains originating in the United States of America and Japan was located in chromosome II. Oppenoorth's work proved that this gene caused the production of the enzyme DDT-dehydrochlorinase, discovered by Sternburg, Kearns, and Moorefield (1954), and indicated the possibility that different alleles of this gene have been selected in strains with various activities of the enzyme. At present it seems likely that the DDT resistance gene of the Canberra colony is allelic with RDDT.…”
Section: Discussionmentioning
confidence: 99%